Influence of physiochemical properties on the subcutaneous absorption and bioavailability of monoclonal antibodies - Amita Datta-Mannan; Selina Estwick; Chen Zhou; Hiuwan Choi; Nicole E. Douglass; Derrick R. Witcher; Jirong Lu; Catherine Beidler; Rohn Millican (Taylor & Francis Group, 2020)
Many therapeutic monoclonal antibodies (mAbs) were initially developed for intravenous (IV) administration. As a means to improve mAb drug-ability and the patient experience, subcutaneous (SC) administration is an increasingly important delivery route for mAbs. Unlike IV administration, bioavailability limitations for antibodies have been reported following SC injection and can dictate whether a mAb is administered via this parenteral route. The SC bioavailability of antibodies has been difficult to predict, and it can be variable and partial, with values ranging from ~50% to 100%. The mechanisms leading to the incomplete bioavailability of some mAbs relative to others are not well understood. There are some limited data that suggest the physiochemical properties inherent to a mAb can contribute to its SC absorption, bioavailability, and in vivo fate. In this study, we evaluated the integrated influence of multiple mAb physiochemical factors on the SC absorption and bioavailability of six humanized mAbs in both rats and cynomolgus monkeys. We demonstrate the physiochemical properties of mAbs are critical to their rate and extent of SC absorption. The combination of high positive charge and hydrophobic interaction significantly reduced the rate of the evaluated mAb's SC absorption and bioavailability. Reduction or balancing of both these attributes via re-engineering the mAbs restored desirable properties of the molecules assessed. This included reduced association with SC tissue, improvements in mAb absorption from the SC space and overall SC bioavailability. Our findings point to the importance of evaluating the relative balance between various physiochemical factors, including charge, hydrophobicity, and stability, to improve the SC drug-ability of mAbs for selecting or engineering mAbs with enhanced in vivo absorption and bioavailability following SC administration.